2018
DOI: 10.1038/s41564-018-0219-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmepsin V cleaves malaria effector proteins in a distinct endoplasmic reticulum translocation interactome for export to the erythrocyte

Abstract: Plasmodium falciparum exports hundreds of virulence proteins within infected erythrocytes, a process that requires cleavage of a pentameric motif called Plasmodium export element or vacuolar transport signal by the endoplasmic reticulum (ER)-resident protease plasmepsin V. We identified plasmepsin V-binding proteins that form a unique interactome required for the translocation of effector cargo into the parasite ER. These interactions are functionally distinct from the Sec61-signal peptidase complex required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 47 publications
2
91
0
Order By: Relevance
“…In all three cases, after a short, 3-hour exposure with 10µM GNF179 (same conditions as above for the reporters for both GNF179 and WEHI-842) (Figure S2), we observed a modest accumulation of all three proteins suggesting impairment of protein export from the parasite (Figure S2). A conditional knockdown of PfSEC62 using the glmS ribozyme system 44,45 showed that parasites were 3-fold more sensitive to GNF179 (0.66 nM for 3D7 wildtype vs 0.24 nM for PfSEC62 kd) (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all three cases, after a short, 3-hour exposure with 10µM GNF179 (same conditions as above for the reporters for both GNF179 and WEHI-842) (Figure S2), we observed a modest accumulation of all three proteins suggesting impairment of protein export from the parasite (Figure S2). A conditional knockdown of PfSEC62 using the glmS ribozyme system 44,45 showed that parasites were 3-fold more sensitive to GNF179 (0.66 nM for 3D7 wildtype vs 0.24 nM for PfSEC62 kd) (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…To begin, we constructed a parasite strain that bears a fusion between the Knob-Associated Histidine Rich Protein and GFP 44 (Figure 5a). The chimeric gene, which bears the first 69 amino acids of KAHRP containing the signal peptide (SP) and PEXEL motif (Px), was expressed from a pfcrt promoter and was integrated into the cg6 locus in Dd2-attB parasites using the attP × attB integrase system 45 . In the absence of GNF179 the GFP reporter was trafficked to the parasitophorous vacuole (PV) as well as to the RBC cytosol, as shown by the GFP staining in the PV surrounding the parasite (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cleavage of the signal sequence in PEXEL proteins has been reported to be inefficient and in other cases has not been observed at all (Boddey et al, ; Boddey et al, ). A study by Marapana et al (Marapana et al, ), which focused on identifying specific PM5‐interacting proteins, has now been able to shed light on why this is the case. Rather than complexing with the canonical PfSec61‐signal peptidase complex (SPC), PM5 is instead associated with a distinct complex that comprises PfSec61 and PfSPC25 but not signal peptidase (Figure ).…”
Section: Discriminating Parasite Proteins Which Need To Be Exportedmentioning
confidence: 99%
“…The distinctive modes of entry into the ER via the Sec61-SPC25 or Sec61-SPC25-PM5 pathways for proteins with canonical ER signal sequences or signal sequences with PEXEL motifs, respectively, may be a mechanism by which the parasite sorts different types of cargo (i.e., secreted versus exported) to distinct locations within the ER that progress into distinct vesicular trafficking pathways (Marapana et al, 2018). Although this would be consistent with the findings from a study that showed failure of a reporter protein to be exported when engineered to create the same N-terminus when cleaved by signal peptidase as PM5 (Boddey et al, 2010), other studies have shown cleavage by signal peptidase or an exogenous protease is sufficient to direct proteins for export (Gruring et al, 2012;Tarr, Cryar, Thalassinos, Haldar, & Osborne, 2013).…”
Section: Discriminating Parasite Proteins Which Need To Be Exportedmentioning
confidence: 99%